Social Ecological Factors of Sexual Subjectivity and Contraceptive Use and Access Among Young Women in the Northwest Territories, Canada. Issue 8 (13th October 2019) - Lys, Candice; Gesink, Dionne; Strike, Carol; Larkin, June
Abstract : Adolescent women in the Northwest Territories (NWT), Canada, experience many sexual health challenges that are linked to a history of colonization and intergenerational effects of trauma. This study was informed by social ecological theory and explored how young women in the NWT develop sexual subjectivity within the context of contraception use and access during this time of decolonization. A total of 41 participants (aged 13 to 17 years) attended the Fostering Open eXpression among Youth (FOXY) body-mapping intervention in six NWT communities and then completed semistructured interviews. Framework analysis identified barriers to the development of sexual subjectivity that included a culture of stigma and shame surrounding sexuality; pervasive alcohol use in communities; predatory behaviors by older men; poor quality sexual health education offered in schools; and issues with accessing health services. In addition, analysis identified the following facilitators: comprehensive sexual health education; widespread access to free condoms; and positive health support networks with female relatives, peers, and some teachers. Our findings suggest the need for multiple intervention strategies within a complex social ecological framework, including arts-based interventions that focus on developing self-esteem and self-efficacy of youth, combined with interpersonal interventions that strengthen communication skills among supportive adults, and community-level campaigns that target stigma reduction and shift cultural norms.